Affective compatibility between stimuli and response goals: a primer for a new implicit measure of attitudes. - Andreas B Eder (Public Library of Science (PLoS), 2013)
We examined whether a voluntary response becomes associated with the (affective) meaning of intended response effects. Four experiments revealed that coupling a keypress with positive or negative consequences produces affective compatibility effects when the keypress has to be executed in response to positively or negatively evaluated stimulus categories. In Experiment 1, positive words were evaluated faster with a keypress that turned the words ON (versus OFF), whereas negative words were evaluated faster with a keypress that turned the words OFF (versus ON). Experiment 2 showed that this compatibility effect is reversed if an aversive tone is turned ON and OFF with keypresses. Experiment 3 revealed that keypresses acquire an affective meaning even when the association between the responses and their effects is variable and intentionally reconfigured before each trial. Experiment 4 used affective response effects to assess implicit in-group favoritism, showing that the measure is sensitive to the valence of categories and not to the valence of exemplars. Results support the hypothesis that behavioral reactions become associated with the affective meaning of the intended response goal, which has important implications for the understanding and construction of implicit attitude measures.